The correlation of CO concentration and green open space (case study of Jagakarsa District, South Jakarta) - Purnomosutji Dyah Prinajati; Ratih Pratiwi (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2022)
Green Open Space serves indirectly to improve the level of public health. One of the sub-districts in South Jakarta is Jagakarsa is a potential area in the development of Green Open Space. Therefore, in this study, ananalysis of the relationship between Green Open Space and carbon was carried out. Determination of the relationship between the area of Green Open Space and CO was carried out using the correlation analysis method. The data used in this study is secondary data in the form of air quality data for five years in South Jakarta Area. Data were processed with SPSS to get the correlation between CO and land used.The results have proven that there is a very strong relationship between Green Open Space and CO with a correlation value of -0,865. Where every decrease in the existing area of Green Open Space/Ruang Terbuka Hijau (RTH) greatly affects CO levels. Based on Law No. 26 of 2007 concerning spatial planning, the minimum proportion of green open space in a city is 30% of the city area, but in Jagakarsa, it is decreased to 10,33 %.